Development of Chitosan/Glutaraldehyde Cross-Linked Film with Silica Addition as Membrane Material for SLS Rejection in Detergent Wastewater - Illiana, Fivi Fatwa; Ariyanto, Hermawan Dwi (Journal of Vocational Studies on Applied Research, 2024)
The pollution resulting from domestic waste has increased with the growing population density, and one of the potential contributors to groundwater contamination is detergent waste. Sodium Lauryl Sulphate (SLS) serves as a common active ingredient in detergent formulations. By leveraging membrane technology, SLS can be processed to reduce its concentration in water to environmentally safe levels. Chitosan, a promising material for membrane composition, is considered as the base material. Exploiting the hydrophilic characteristics of chitosan, silica is introduced to enhance membrane selectivity by reducing pore size through cross-linking between chitosan and silica molecules. The performance of the silica-modified membrane is then evaluated through tests measuring the rejection coefficient against SLS, membrane swelling degree, morphological profiling of functional groups using FTIR, and tensile strength measured with a Universal Testing Machine. Subsequently, the membrane's efficiency in rejecting SLS in detergent waste is assessed based on rejection coefficients using an SLS solution model.